2023
DOI: 10.46542/pe.2023.231.216222
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative perspective on the correlation between students’ cumulative grade point average and their results in the Doctor of Pharmacy programme in Saudi Arabia

Abdulkareem M. Albekairy,
Aiman A. Obaidat,
Abdulmajeed A. Alqasomi
et al.

Abstract: Background: The colleges of pharmacy in Saudi Arabia share a set of unified programme learning outcomes for their Doctor of Pharmacy (Pharm.D.) programmes. Based on this, a unified progress test for pharmacy students has been implemented over the past five years. The aim of this study is to correlate the students’ results in the test to their cumulative grade point average (cGPA). Methods: The progress test is usually composed of 100 multiple choice questions, 30 of which cover basic pharmaceutical sciences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…In the same vein as the finding of the current study's outcomes, the College of Medicine at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) identified a positive correlation between progress test results and students' CGPAs by AlAlwan et al(2011). Another study byAlbekairy et al (2023) revealed a positive correlation between the students' PT results and their CGPA.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In the same vein as the finding of the current study's outcomes, the College of Medicine at King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) identified a positive correlation between progress test results and students' CGPAs by AlAlwan et al(2011). Another study byAlbekairy et al (2023) revealed a positive correlation between the students' PT results and their CGPA.…”
mentioning
confidence: 90%
“…First-year students scored 3.0% to 7.9%, and fifth-year students 34.0% to 43.0%. Similarly,Albekairy et al (2021Albekairy et al ( & 2023 investigated the students' overall outcomes. They reported that all 16 pharmacy colleges that participated in the study experienced a significant improvement in the percentage of students' PT scores as they progressed through the professional years of the program, indicating students' growth in knowledge retention and skill development.…”
mentioning
confidence: 99%